Evolution of Antimicrobial Consumption During the First Wave of COVID-19 Pandemic - Santiago Grau; Daniel Echeverria-Esnal; Silvia Gómez-Zorrilla; Maria Eugenia Navarrete-Rouco; Joan Ramon Masclans; Merce Espona; Maria Pilar Gracia-Arnillas; Xavier Duran; Merce Comas; Juan Pablo Horcajada; Olivia Ferrández (MDPI AG, 2021)
Background: The first wave of COVID-19 pandemic may have significantly impacted antimicrobial consumption in hospitals. The objective of this study was to assess the evolution of antimicrobial consumption during this period. Methods: A retrospective quasi-experimental before-after study was conducted in a Spanish tertiary care hospital. The study compared two periods: pre-pandemic, from January 2018 to February 2020, and during the COVID-19 pandemic from March to June 2020. Antimicrobial consumption was analyzed monthly as defined daily doses (DDD)/100 bed-days and overall hospital and ICU consumption were evaluated. Results: An increase in the hospital consumption was noticed. Although only ceftaroline achieved statistical significance (p = 0.014), a rise was observed in most of the studied antimicrobials. A clear temporal pattern was detected. While an increase in ceftriaxone and azithromycin was observed during March, an increment in the consumption of daptomycin, carbapenems, linezolid, ceftaroline, novel cephalosporin/β-lactamase inhibitors or triazoles during April-May was noticed. In the ICU, these findings were more evident, namely ceftriaxone (p = 0.029), carbapenems (p = 0.002), daptomycin (p = 0.002), azithromycin (p = 0.030), and linezolid (p = 0.011) but followed a similar temporal pattern. Conclusion: An increase in the antimicrobial consumption during the first wave of COVID-19 pandemic was noticed, especially in the ICU. Availability of updated protocols and antimicrobial stewardship programs are essential to optimize these outcomes.